Computing the maximum violation of a Bell inequality is an NP-problem - Batle, J.; Raymond Ooi, C.H.; Abdalla, S.; Bagdasaryan, A. (Springer Verlag (Germany), 2016)
The number of steps required in order to maximize a Bell inequality for arbitrary number of qubits is shown to grow exponentially with the number of parties involved. The proof that the optimization of such correlation measure is an NP-problem based on an operational perspective involving a Turing machine, which follows a general algorithm. The implications for the computability of the so-called nonlocality for any number of qubits is similar to recent results involving entanglement or similar quantum correlation-based measures.